Generation and validation of a prognostic score to predict outcome after re-irradiation of recurrent glioma - Combs, Stephanie; Edler, Lutz; Welzel, Thomas; Wick, Wolfgang; Debus, Jürgen (Acta oncologica, 2013)
Re-irradiation using high-precision radiation techniques has been established within the clinical routine for patients with recurrent gliomas. In the present work, we developed a practical prognostic score to predict survival outcome after re-irradiation. Patients and methods. Fractionated stereotactic radiotherapy (FSRT) was applied in 233 patients. Primary histology included glioblastoma (n = 89; 38%), WHO Grade III gliomas (n = 52; 22%) and low-grade glioma (n = 92; 40%). FSRT was applied with a median dose of 36 Gy in 2 Gy single fractions. We evaluated survival after re-irradiation as well as progression-free survival after re-irradiation; prognostic factors analyzed included age, tumor volume at re-irradiation, histology, time between initial radiotherapy and re-irradiation, age and Karnofsky Performance Score. Results. Median survival after FSRT was 8 months for glioblastoma, 20 months for anaplastic gliomas, and 24 months for recurrent low-grade patients. The strongest prognostic factors significantly impacting survival after re-irradiation were histology (p < 0.0001) and age (< 50 vs. ≥ 50, p < 0.0001) at diagnosis and the time between initial radiotherapy and re-irradiation ≤ 12 vs. > 12 months (p < 0.0001). We generated a four-class prognostic score to distinguish patients with excellent (0 points), good (1 point), moderate (2 points) and poor (3-4 points) survival after re-irradiation. The difference in outcome was highly significant (p < 0.0001). Conclusion. We generated a practical prognostic score index based on three clinically relevant factors to predict the benefit of patients from re-irradiation. This score index can be helpful in patient counseling, and for the design of further clinical trials. However, individual treatment decisions may include other patient-related factors not directly influencing outcome.